Bio-based epoxy resin toughening with cashew nut shell liquid-derived resin. Issue 3 (4th September 2015) - Maiorana, Anthony; Ren, Liyun; Lo Re, Giada; Spinella, Stephen; Ryu, Chang Y.; Dubois, Philippe; Gross, Richard A.
Abstract : With the combinations of diglycidyl ether diphenolate methyl ester (DGEDP-Me), a rigid high-viscosity bio-based epoxy resin and a flexible lower viscosity epoxy resin from cashew nut shell liquid (NC-514), resin viscosity was controlled and important improvements were realized in cured epoxy resin toughness relative to the neat resins. The viscosities of DGEDP-Me/NC-514 mixtures varied from 660 to 26 Pa.s, and curing was performed using stoichiometric amounts of a diamine cross-linker. Using scanning electron microscopy analysis of fractured surfaces, the cured materials were shown to be one-phase. Furthermore, all resin compositions were transparent and have one alpha transition temperature, confirming resin miscibility. Storage modulus values for cured thermosets range from 3000 to 1000 MPa, and alpha transition temperatures varied linearly (158 to 27°C) as a function of the epoxy resin composition. Oscillatory rheology at different weight percentages of the flexible and rigid epoxy resin components was used to determine the average molecular weight between cross-links which was correlated to material toughness. Relative to the neat high-viscosity resin, 1:1 wt/wt mixtures of the rigid and flexible epoxy resin components gave increases in the impact strength and mode I fracture toughness of 136 and 66%, respectively. Higher percentages of the flexible epoxy resin resulted in decreased toughness.